Juridical Analysis of the Crime of Illegal Cigarette Distribution According to the Excise Law - Putra Nurdiansyah, Nanda; Dudik Djaja Sidarta; Dedi Wardana Nasution (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
This study is titled “Juridical Analysis of the Crime of Distributing Illegal Cigarettes According to Law on Excise” and is motivated by the widespread distribution of cigarettes without excise stamps or with counterfeit stamps, which causes state losses and disrupts economic order. The main issues examined are, first, how the legal regulations regarding excise and illegal cigarettes are according to Law Number 39 of 2007, and second, what forms of criminal liability apply to perpetrators of illegal cigarette distribution under this law. This study uses a normative juridical method with a legislative and conceptual approach, relying on primary legal materials in the form of regulations related to excise, as well as secondary legal materials in the form of books, journals, and other scientific documents. The results of this study indicate that Law No. 39 of 2007 has clearly regulated criminal sanctions for violations in the field of excise, particularly through the provisions of Articles 54 and 56, however, its implementation still faces challenges in terms of supervision and law enforcement. This research is expected to serve as a reference for improving policies to combat the circulation of illegal cigarettes and enhancing the effectiveness of excise law enforcement.